Integrating Islamic Values into Bullying Prevention: A Public Health Approach in Indonesian Schools - Ali, Shahzad; Naz, Iqra (Knowledge Dynamics, 2025)
Bullying is a rising public and mental health issue, especially in students and is linked to depression, anxiety, low self-esteem, and suicide attempts. In Indonesia, the cases are on the rise, which lends credence to the fact that prevention strategies should be culturally relevant. This paper uses a literature-based and theoretical approach to investigate bullying in the context of a public health model and the suggestions of Islamic teachings as a prevention tool. The research provides both theoretical and contextual originality in the combination of Islamic ethical ideals, including dignity, non-violence and accountability, with the modern models of bullying prevention. The evidence indicates that Islamic teachings offer culturally based and novel framework to supplement evidence-based interventions. The method is useful to a teacher, policy makers and community leaders in formulating effective anti-bullying policies and foster the psychological well-being of students.